2013
DOI: 10.1530/eje-13-0569
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Cushing's syndrome: systematic analysis of a large series with prolonged follow-up

Abstract: Objective: In this study, we aim to assess the long-term survival and causes of death in a retrospective cohort study on patients with all aetiologies of endogenous Cushing's syndrome (CS) (except adrenal cancer), presenting to two large tertiary endocrine referral centres, and to identify variables predicting mortality. Results: In total, 418 subjects were identified (311 with Cushing's disease (CD), 74 with adrenal Cushing's (AC) and 33 with ectopic Cushing's (EC)). In CD, the probability of 10-year survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 26 publications
(47 reference statements)
3
107
2
2
Order By: Relevance
“…Cushing syndrome (CS) is a clinical state of prolonged exposure to inappropriately high levels of exogenous or endogenous glucocorticoids and is associated with significant morbidity and mortality (1)(2)(3)(4)(5). Surgical resection of the causal tumor(s) remains the first-line therapy for endogenous CS.…”
Section: Introductionmentioning
confidence: 99%
“…Cushing syndrome (CS) is a clinical state of prolonged exposure to inappropriately high levels of exogenous or endogenous glucocorticoids and is associated with significant morbidity and mortality (1)(2)(3)(4)(5). Surgical resection of the causal tumor(s) remains the first-line therapy for endogenous CS.…”
Section: Introductionmentioning
confidence: 99%
“…These patients typically suffer from ectopic Cushing's syndrome. They might develop, in addition to classical Cushing's stigmata, life-threatening complications of hypercortisolism, such as bacteraemia and sepsis (27,28,29), thromboembolic complications, intractable hypokalaemic hypertension, heart failure, gastrointestinal haemorrhage, psychosis, debilitating myopathy, uncontrolled hyperglycaemia or a combination of these conditions (30). Serum cortisol levels generally reach 41 mg/dl (1100 nmol/l) and may be even higher than 100 mg/dl (2700 nmol/l).…”
Section: When Is Badx In Acth-dependent Cushing's Syndrome Indicated?mentioning
confidence: 99%
“…Patients with persistent or recurrent disease show a dramatically increased mortality compared to the general population, while patients who obtain the surgical remission seem to have a mortality rate similar to that of general population, even though some discrepancies have been reported [13]. Indeed, different retrospective studies reported a maintained increased mortality compared to general population, even in patients who achieved the remission [14][15][16], due to the persistence of several comorbidities and strongly dependent on the duration of exposure to glucocorticoid excess.…”
Section: Introductionmentioning
confidence: 98%